MAKNA TRADISI BAKAR BATU SUKU DANI (Studi Etnografi Di Kalangan Masyarakat Kampung Alang-Alang V Kabupaten Keerom Papua) - Kotib, Seto Aji Nur; DS, Vina Salviana; Kumalasari, Luluk Dwi (Sosial Budaya, 2022)
Indonesia is an archipelagic country with ethnic, cultural, and linguistic diversity. Papua is an island as well as a province at the eastern tip of Indonesia. Papua has various ethnic groups, one of which is the Dani tribe from the Baliem Valley of the Central Mountains. The Dani tribe has a culture or tradition that is carried out when commemorating an event that occurs. One of these traditions is the Burning Stone or Barapen Tradition. The Dani tribe began to live and occupy other areas, one of which was in Kampung Alang-Alang V. The research formulation was to determine the Meaning of the Dani Tribe Bakar Batu Tradition among the People of Kampung Alang-Alang V. This study used a qualitative approach with ethnographic methods. Ethnography is used to find out the meaning of the Dani culture among the Alang-Alang V people in the form of the Bakar Batu Tradition. By analyzing using Symbolic Interactionalism Theory. The meaning of the Burning Stone Tradition carried out by the Dani Tribe has the following meanings: 1.) As conflict peace, 2). Ancestral traditional values, 3). Group Identity, 4.) The form of gratitude, and 5). The Bakar Batu Tradition Media carried out by the Dani Tribe Community in Alang-Alang V Village cannot be separated from the translation of ancestral symbols and values conveyed by parents to the younger generation, in order to continue to preserve the tradition.